Prognosis in Thymoma Patients with Myasthenia Gravis Undergoing Video-Assisted Thoracoscopic Surgery (VATS) Thymectomy: An Evidence-Based Case Report - Mety, Susan Hendriarini; Permadijana, Diajeng; Ramli, Muhammad Syawal Satria (Jurnal Respirologi Indonesia, 2025)
Background: Thymoma, a tumor in the anterior mediastinum, is common in adults and often linked with myasthenia gravis (MG). Thymectomy is recommended for MG patients with thymoma and traditionally done via median sternotomy, which is invasive. Minimally invasive methods like video-assisted thoracoscopic surgery (VATS) offer benefits like less blood loss and quicker recovery. However, more extensive studies are needed to confirm long-term oncological outcomes. Methods: A literature search was conducted using PubMed, Cochrane, and Scopus databases focused on terms related to thymoma, myasthenia gravis, VATS thymectomy, and survival. Duplicates were excluded, and studies were selected based on criteria. The selected studies were then critically appraised for validity, importance, and applicability. Results: Three manuscripts are selected for this case report. He et al showed that the cumulative CSR in the VATS group (26.7%) was significantly higher than the transsternal group (P=0.026). Maggi et al reported that the VATS group is significantly correlated with CSR (P=0.0349). Meanwhile, Tian et al showed there was no significant difference in the level of CSR (32.7% vs. 36.7%; P=0.622) between the VATS and trans-sternal groups. Tian et al also showed that survival results in the VATS group were higher than in the trans-sternal group, but it was not statistically significant (P=0.109). Conclusion: The prognosis of thymoma patients with MG who undergo thymectomy using the VATS method is not significantly different compared with the trans-sternal method.